A iconoclastia da natureza - Sousa, Celeste H. M. Ribeiro de (In:Pandaemonium Germanicum;São Paulo : Humanitas Publicações, 1997-2006;Band 1, Heft 1 (1997), Seite 67-76;22 cm, 1997)
In expressionist poetry we can detect a first major rupture in the relations between man and nature. In expressionist poems such as
urn:nbn:de:hebis:30:3-259603
Keywords: Online-Publikation; Hoddis; Jakob van; Kirsch; Sarah; Naturlyrik; Expressionismus; Umweltverschmutzung